2023
DOI: 10.3389/fmars.2022.1070078
|View full text |Cite
|
Sign up to set email alerts
|

A sustainable shipping management framework in the marine environment: Institutional pressure, eco-design, and cross-functional perspectives

Abstract: The shipping industry plays a vital role in the world trading system and in maintaining the stability of global supply chains. However, we cannot ignore the damage it brings to the marine environment. With a focus on protecting the marine environment, the sustainable development of shipping companies has also drawn growing attention. This study examines the sustainable shipping management practice system and develops a comprehensive framework to evaluate the significance of influencing elements and prioritizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…The manufacturing and distributing biofuels and installing offshore wind farms are two examples of activities that can potentially damage aquatic ecosystems and habitats. Careful planning and extensive environmental impact studies are required to minimize these consequences and ensure the deployment of these technologies in a sustainable manner [126], [127].…”
Section: B Policy Suggestions 1) Environmental Implicationsmentioning
confidence: 99%
“…The manufacturing and distributing biofuels and installing offshore wind farms are two examples of activities that can potentially damage aquatic ecosystems and habitats. Careful planning and extensive environmental impact studies are required to minimize these consequences and ensure the deployment of these technologies in a sustainable manner [126], [127].…”
Section: B Policy Suggestions 1) Environmental Implicationsmentioning
confidence: 99%
“…It is suggested that future research should be conducted using longitudinal research designs. For example, cross-functional studies could be developed for companies to improve their management framework [86]. This research has been conducted in the electronic industry only.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…In countries that have not yet implemented a GHWLs policy, this policy should be implemented as soon as possible to warn the public more effectively about the dangers of smoking. This requires borrowing the power of the institution and legislating to solve the problem (Wang et al, 2023).…”
Section: Policy Implicationsmentioning
confidence: 99%